Formal vs informal: Public participation in village government development planning in Indonesia — Evidence from Bumiwangi Village - Syifana, Annisa; Halim, Abdul; Lestari, Sindy Fuji (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: This study examines how public participation is implemented in village development planning and investigates the factors contributing to its limited effectiveness.Design/Methodology/Approach: Using a qualitative case study approach, this research applies Miller et al.’s (2019) framework of participation modes to analyze the operation of formal and informal participatory mechanisms in village governance. Fieldwork was conducted in Bumiwangi Village, West Java, through semi-structured interviews, participant observation, and document analysis to assess how participatory practices influence accountability and decision-making.Research findings: The study identifies two interconnected models of public participation. Formal participation occurs through village development planning deliberations (Musrenbangdes), while informal participation takes place in community deliberation forums (rembug warga). Informal participation is characterized by openness, inclusivity, and deliberative dialogue that enables collective problem-solving and meaningful citizen input. In contrast, formal participation is largely dominated by selected representatives and confirmatory communication aligned with the village head’s agenda, resulting in limited citizen influence. Public input is mostly indirect and exercised through informal spaces rather than formal decision-making channels. Two key barriers constrain effective participation: (1) village authorities’ narrow understanding of participation as mere representation, and (2) limited public access to financial and planning information, which restricts informed and critical engagement.Theoretical contribution/Originality: This study extends Miller et al.’s (2019) participation framework to a rural Indonesian context, highlighting the structural weaknesses of formal participatory mechanisms and emphasizing the crucial yet underrecognized role of informal forums in fostering deliberative accountability and social legitimacy.Practitioner/Policy implication: Policymakers should integrate informal participatory forums into formal governance processes, enhance transparency, and expand public access to information to reduce elite dominance and strengthen accountability.